Investigation of the measurement of through-thickness residual stress by combining digital speckle pattern interferometry and the slitting method - Ospina Pineda, Oscar Javier (2020)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2020.